Performance analysis in team sports - Passos, Pedro; Araújo, Duarte; Volossovitch, Anna (Routledge studies in sports performance analysis, 2017)
Filling an important gap in performance analysis literature, this book introduces the key concepts and practical applications of performance analysis for team sports. It draws on cutting-edge research to examine individual and collective behaviours across an array of international team sports. Evidencing the close relationship between coaching and performance analysis, it promotes a better understanding of the crucial role of performance analysis in team sports for achieving successful results. This book not only presents a variety of different ways to analyse performance in team sports, but also demonstrates how scientific data can be used to enrich performance analysis. Part one delineates the main guidelines for research in performance analysis, discussing the characteristics of team sports, coaching processes, variables characterizing performance and methods for team member interaction analysis. Part two drills down into performance analysis across a range of team sports including soccer, basketball, handball, ice hockey, volleyball and rugby. Performance Analysis in Team Sports is an essential companion for any course or research project on sports performance analysis or sports coaching, and an invaluable reference for professional analysts.